Pengembangan Bahan Ajar Augmented Reality Berbantuan Assemblr Edu pada Materi Kondisi Perekonomian di Daerahku - Amelia; Wawan Syahiril Anwar; Nurlinda Safitri (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The rapid development of digital technology has encouraged teachers to develop innovative teaching materials that can improve students' engagement and understanding. However, learning in elementary schools is still frequently dominated by printed teaching materials and teacher-centered instruction, resulting in limited opportunities for students to experience interactive and meaningful learning. The integration of Augmented Reality (AR) technology through Assemblr Edu offers an alternative for presenting learning materials in a more concrete, visual, and engaging way. This study aimed to develop Augmented Reality -based teaching materials supported by Assemblr Edu for the topic Economic Conditions in My Region and to determine their feasibility and effectiveness. The study employed Research and Development using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation. The research was conducted at SDN Bantarkemang 1, Bogor City. A limited trial involved 20 fifth-grade students, while product validation involved four validators representing material, language, and media expertise. Data were collected through observation, interviews, questionnaires, documentation, and a 19-item learning achievement test. The final validation scores were 94% from the lecturer material expert, 96% from the teacher material expert, 90% from the language expert, and 98% from the media expert, with an average of 95% in the highly feasible category. Student and teacher responses reached 90% and 96%, respectively. The mean score increased from 41.05 on the pretest to 83.68 on the posttest, and the N-gain score was 0.71, categorized as high. Therefore, the developed teaching materials were highly feasible and effective in improving learning outcomes in the limited trial.